Civic capital and support for the welfare state - Roy Cerqueti; Fabio Sabatini; Marco Ventura (Economics and Econometrics Research Institute (EERI), 2017)
We model how the interplay between tax surveillance institutions and civic capital shapes taxpayers' support for welfare state. We show that, when tax surveillance is tight, rational civic-minded individuals express greater support for welfare spending than uncivic ones. We provide empirical evidence of these preferences using data from Italy, a country that has long posed a puzzle for public economists for its limited civic capital and large welfare state.
Keywords: H10; H53; D63; D69; Z1; 330; Welfare state; redistribution; tax surveillance; trust; civic capital; social capital